Football coaching leadership style in Malaysia: an exploratory factor analysis / Azlina Zid ... [et al.] - Zid, Azlina; Wahab, Siti Aishah; Shaari, Jamatul Shahidah; Mohd Nor, Maizan; Rajli, Mohammad Adzly; Abd Latif, Rozita; Amiruddin, Rozita (Universiti Teknologi MARA, 2023)
This study aims at identifying the constructs in the Leadership Scale for Sport (LSS) from the perspective of Malaysian football players. To date, empirical study of factor analysis on coaching leadership style construct in a sports setting is limited. There are 330 professional football players from the Malaysian Super and Premier League who were involved in this study. Leadership Scale for Sport (LSS) by Chelladurai and Saleh (1980) was used, and the exploratory factor analysis was done to obtain information on this current study. The findings showed that from 40 items that measure the five constructs of a coach's style, only 24 items had been formed. However, the five constructs remain. The extraction revealed the five constructs gave a higher eigenvalue than 1, and cumulatively contributed approximately 70.44% overall variance changes for the coach's leadership style variable. Through the rotated sums of squared loadings analysis, the five constructs predicted as much as 77.47% overall change of variance for the variable coaching leadership style are Factor 1=17.36%; Factor 2=16.09%; Factor 3=14.56%; Factor 4=11.88% and Factor 5=10.55%